SUFISM AS THE SPIRITUAL FOUNDATION OF ANTI-FEUDALIST DA'WAH: A CRITIQUE OF HIERARCHICAL SOCIAL STRUCTURES - Yuspitasari, Selvy; Basri, Hasan (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2026)
This study critically examines the potential of Sufism as a spiritual and ethical foundation for anti-feudalist da’wah in Islamic social thought. Feudalism, understood not merely as a historical socio-economic system but as a persistent hierarchical mentality, continues to legitimize social inequality, patronage, and the glorification of worldly status in modern societies. In response, this article posits that Sufism—with its core principles of tawadhu‘ (humility), zuhud (detachment from worldly obsession), ikhlas (sincerity), and ukhuwwah (spiritual brotherhood)—offers a profound spiritual critique of such hierarchical structures. Through a qualitative literature review of classical Sufi works by Al-Ghazali, Ibn ‘Arabi, and Rumi, as well as contemporary analyses, this research demonstrates how Sufi ontology and ethics deconstruct feudal logic by affirming the ontological equality of all human beings before God. The concept of tawhid (divine oneness) is reinterpreted not only as a theological axiom but as a social principle that negates any form of human domination. Furthermore, the article highlights how Sufi teachings foster a form of da’wah that is inherently emancipatory, promoting social justice, moral accountability, and egalitarian consciousness. By purifying the self from spiritual diseases such as kibr (arrogance) and hubb al-jah (love of status), Sufism cultivates a socio-spiritual awareness that challenges both feudal legacies and their modern manifestations. Thus, this paper concludes that Sufism provides a transformative framework for da’wah that seeks not only personal piety but also the establishment of a just and non-hierarchical social order rooted in divine love and moral integrity.